The association between lichen planus and hepatitis C virus infection: A case control study - G Rai Subodha Kumar; Nagesha Parvathi; RangeGowda Suresh; Rangaswamy Umadevi; Nirvanappa Vinay (Our Dermatology Online, 2021)
Background: The incidence of Hepatitis C virus (HCV) infection among patients with Lichen planus (LP) varies considerably. There is also lack of data in Indian population. Due to these variation, this study is to assessing the prevalence of HCV infection among patients with CLP in Hassan Karnataka. Methods: 135 clinically diagnosed cases of Lichen planus more than 18 years of age will be included as cases.147 patients having skin diseases other than lichen planus will be included as controls. Details of the patients personal history and family history,medical history and blood transfusion history will be collected. Detection of antibodies against HCV (anti-HCV) by enzyme-linked immunosorbent assay (ELISA). Results: Anti-HCV antibodies were found in 3(2.2%) patients of the case group and 1(0.7%) in control group. P value is 0.274, not statistically significant. Conclusion: Currently, there is no evidence confirming the relationship between HCV infection and CLP in Hassan Karnataka. However, there is a need for further research on larger groups of